Humor sebagai pedagogi etis di perguruan tinggi Indonesia: pengalaman mahasiswa, jenis humor efektif, dan strategi pengajaran berorientasi SDG 4 - Taufikin Taufikin; Sri Nurhayati; Habib Badawi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2025)
A rigid and stressful classroom environment can reduce students’ motivation and increase academic anxiety. Humour in learning serves as an effective pedagogical strategy to enhance engagement, reduce tension, and strengthen memory retention. However, not all types of humour positively influence the learning process. This study aims to identify the most effective types of humour and optimal strategies for their implementation in Indonesian higher education. Employing a qualitative-phenomenological approach, data were collected through structured interviews with 40 students from multiple universities. The findings reveal that academic humour is the most effective in improving comprehension and retention, while spontaneous humour promotes student engagement. In contrast, irrelevant or excessive humour tends to distract students from their focus. The study's novelty lies in integrating Islamic educational values with Western educational psychology to explain the role of humour in fostering a balanced, enjoyable, and ethically guided learning environment. The research aligns with Sustainable Development Goal 4 (Quality Education) by emphasizing the importance of inclusive and engaging pedagogical practices that enhance the quality of learning in higher education. The study also provides practical recommendations for lecturers to apply humour responsibly as a pedagogical tool that supports motivation, engagement, and meaningful learning.